2020
DOI: 10.1111/tbed.13751
|View full text |Cite
|
Sign up to set email alerts
|

Bats and humans during the SARS‐CoV‐2 outbreak: The case of bat‐coronaviruses from Mexico

Abstract: The novel SARS-CoV-2 coronavirus has attracted attention due to the high number of human cases around the world. It has been proposed that this virus originated in bats, possibly transmitted to humans by an intermediate host, making bats a group of great interest during this outbreak. Almost 10% of the world's bat species inhabit Mexico, and 14 previous novel CoVs have been recorded in Mexican bats. However, the phylogenetic relationships between these viruses and the novel coronavirus are unknown.The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Two phylogenetic analyses were performed, and the best substitution model was evaluated differentially, following the recommendations by Colunga-Salas and Hernández–Canchola [ 48 ]. The first phylogenetic approach was evaluated in IQ-TREE [ 49 ], and the best-fit substitution model was assessed with the ModelFinder algorithm [ 50 ], considering a full-tree search for each model and the Bayesian information criterion (BIC).…”
Section: Methodsmentioning
confidence: 99%
“…Two phylogenetic analyses were performed, and the best substitution model was evaluated differentially, following the recommendations by Colunga-Salas and Hernández–Canchola [ 48 ]. The first phylogenetic approach was evaluated in IQ-TREE [ 49 ], and the best-fit substitution model was assessed with the ModelFinder algorithm [ 50 ], considering a full-tree search for each model and the Bayesian information criterion (BIC).…”
Section: Methodsmentioning
confidence: 99%
“…Although highly important to prevent future similar spill-over transmissions of related viruses ( Wong et al, 2020 ), neither SARS-CoV-2 nor an immediate precursor coronavirus in animals has been reported. Nevertheless, given the sequence similarity of about 96% between SARS-CoV-2 and the betacoronaviruses RaTG13 found in Rinolophus affinus (intermediate horseshoe bats) in China ( Zhou et al, 2020 ), and the detection of a wide range of further coronaviruses in bats (order Chiroptera ) ( Colunga-Salas and Hernández-Canchola, 2020 ; Lacroix et al, 2020 ; Lau et al, 2005 ; Li et al, 2005 ; Wacharapluesadee et al, 2021 ; Yadav et al, 2020 ), bats are suspected to be the reservoir host for the progenitor virus of SARS-CoV-2 ( Latinne et al, 2020 ; Lu et al, 2020a ; Wacharapluesadee et al, 2021 ; Zhou et al, 2020 ).…”
Section: Reservoir and Intermediate Hostsmentioning
confidence: 99%
“…Recent phylogenetic data show that the SARS-CoV-2 coronavirus, which has caused the current COVID-19 pandemic, is not closely related to some Mexican bat coronaviruses (61). However, it is urgent to examine the phylogenetic closeness of SARS-CoV-2 with the rest of the bat coronavirus species and to help clarify the potential to infect humans or other wildlife species and to spread on a large scale, since the ongoing COVID-19 pandemic has demonstrated that advances in knowledge are needed to predict future viral outbreaks [61,62]. Studies like this one aim to improve our understanding of the coronaviruses that bats harbor, not to focus attention on them to incite their slaughter in retaliation for the coronaviruses they harbor.…”
Section: Coronavirus Host Batsmentioning
confidence: 99%